A comparative study on cutting forces and power consumption in plain and ultrasonic vibration helical milling of AISI 1020 steel. (November 2022) - Rao, Kaki Venkata; Prasad, Vookoti Uma Sai Vara; Ben, Beera Satish
The present study aimed to implement a sustainable machining method to improve energy efficiency in helical milling (HM) of AISI 1020. Therefore, ultrasonic vibration is integrated with conventional helical milling to reduce cutting forces. A model was developed for power consumption in terms of cutting forces in x, y and z directions, tangential and axial feed speeds. Series of plain and ultrasonic vibration helical milling (UVHM) experiments are conducted using 10 and 8 mm diameter mill cutters at different working conditions and experimental results for cutting forces are collected. Formation of chip and its geometry are investigated using the cutting trajectories of the bottom cutting edges of the cutter. Cutting forces and power consumption are estimated related to chip geometry in plain and UVHM processes and compared. In UVHM, the axial force is reduced by around 47% as the ultrasonic vibration is applied in the axial direction and the power consumption is reduced by 34%. The results showed that ultrasonic vibration has a significant effect on chip morphology, cutting force and power consumption, indicating that ultrasonic vibration assisted machining has a wide application in manufacturing. The process parameters are optimised as 2000 rpm of cutter rotational speed, 156 rpm of cutter orbital speed and 0.3 mm of axial depth of cut using 8 mm diameter cutter and the chip thickness, chip depth and power consumption are found to be 0.3969 mm, 0.2665 mm and 835.6 W respectively at optimal working condition.